Apology and Unintended Harm in Global Health - David G. Addiss; Joseph J. Amon (Harvard FXB Center for Health and Human Rights, 2019)
Over the past few decades, investments in global health programs have contributed to massive advances in health for human populations. As with clinical medicine, however, global health interventions sometimes result in unintended harm, economic adversity, or social disruption. In clinical medicine, when medical error occurs, it is increasingly common for health care workers to offer apology, which involves acknowledging the error, taking responsibility for it, and expressing genuine remorse. In addition, hospitals are beginning to offer affected patients and their families reparation or compensation in an attempt to restore patients' health and repair relationships, as well as take steps to prevent similar harm in the future. By contrast, little is known about apology and reparation for unintentional harm in global health practice. Several factors, including the scale of global health programs, diffusion of responsibility across international networks of state and non-state actors, and concern that acknowledging harm could threaten otherwise successful health programs, render apology and reparation in global health more difficult than in clinical medicine. This article examines how and when individuals and global health organizations address inadvertent harm, illustrated by four case studies. It also describes ethical, legal, and human rights principles that could inform a more systematic approach. Addressing unintended harm in global health requires further attention at the individual, organizational, and global levels.